(3fLGI GdYHGOs - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3cJGH GdWgGQI, hajg ebOeI hKdGKI ebGUO hNGJeI, CeG GdebOeI aajgG aUdGf, GdChd aj GdejGgs
(3BNQgG (B:s
(3BNQgG(B: (3hEf cGf jbhj aj GdfXQ GdLhGR aj GdRhLI NUhUG EPG de jefY efg Mbg Ch cGf fGTRG Ch ZGFHG Ch fMh Pdc Hd bO jbhd GdLhGR eY Pdc eY Gdfgj aVdG Yf YOe GdEPfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B24: 39s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis